2017
DOI: 10.1038/nature21047
|View full text |Cite
|
Sign up to set email alerts
|

A competitive inhibitory circuit for selection of active and passive fear responses

Abstract: When faced with threat, the survival of an organism is contingent upon the selection of appropriate active or passive behavioural responses. Freezing is an evolutionarily conserved passive fear response that has been used extensively to study the neuronal mechanisms of fear and fear conditioning in rodents. However, rodents also exhibit active responses such as flight under natural conditions. The central amygdala (CEA) is a forebrain structure vital for the acquisition and expression of conditioned fear respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
464
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 411 publications
(500 citation statements)
references
References 36 publications
31
464
4
1
Order By: Relevance
“…Because of the methods used to collect LCM neurons, we were unable to assess protein levels of PKCd in the animals used for RNA-Seq. Studies in the mouse demonstrate that CeL PRKCD expressing neurons are a component of a microcircuit that gates CeL output, modulating the expression of freezing and other threat-related behaviors Fadok et al, 2017;Haubensak et al, 2010;Li et al, 2013;Yu et al, 2016). Because little is known in primates about the proportion and distribution of CeL neurons that express PKCd protein, in three other animals, we systematically characterized CeL PKCd expressing neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the methods used to collect LCM neurons, we were unable to assess protein levels of PKCd in the animals used for RNA-Seq. Studies in the mouse demonstrate that CeL PRKCD expressing neurons are a component of a microcircuit that gates CeL output, modulating the expression of freezing and other threat-related behaviors Fadok et al, 2017;Haubensak et al, 2010;Li et al, 2013;Yu et al, 2016). Because little is known in primates about the proportion and distribution of CeL neurons that express PKCd protein, in three other animals, we systematically characterized CeL PKCd expressing neurons.…”
Section: Discussionmentioning
confidence: 99%
“…While PKCd has been extensively studied in the rodent CeL (Amano et al, 2012;Cui et al, 2017;Haubensak et al, 2010;Ye and Veinante, 2019;Yu et al, 2016), little is known about its expression in the nonhuman primate amygdala. Rodent studies demonstrate that other CeL neurons exist (Cassel and Gray, 1989;McCullough et al, 2018;Price et al, 1987;Roberts et al, 1982) and recent mouse studies reveal that SST expressing GABAergic neurons interact with and modulate the function of PRKCD expressing neurons (Fadok et al, 2017;Kim et al, 2017;Li et al, 2013). Because these cell types have not been well characterized in the nonhuman primate, we used stereological cell counting techniques to map the distribution of PKCd and SST expressing neurons in the rhesus CeL.…”
Section: Characterizing Pkcd and Sst Neurons In The Nonhuman Primate Celmentioning
confidence: 99%
“…While these projections have been known for some time now, studies have begun to identify circuits within the central nucleus that govern whether active or passive fear responses are expressed (e.g., Gozzi et al 2010). Other recent work has identified specific cell types in the central nucleus which favor the expression of passive fear behavior (i.e., freezing), while other cell types drive the expression of active fear responses (Yu et al 2016;Fadok et al 2017). It is tempting to speculate that the balance of these mechanisms might be shifted in females such that they are more likely to engage in active fear responses.…”
Section: Discussionmentioning
confidence: 99%
“…To illustrate this point, consider a recent study targeting local central amygdala circuits involved in selecting between active and passive fear responses (flight vs. freeze) [76]. A major finding of the study was that it revealed inhibitory connections between two subpopulations of central amygdala cells linked to the two behaviors.…”
Section: Implications For Emotion Researchmentioning
confidence: 99%